1997
DOI: 10.1073/pnas.94.9.4794
|View full text |Cite
|
Sign up to set email alerts
|

A membrane-anchored E-type endo-1,4-β-glucanase is localized on Golgi and plasma membranes of higher plants

Abstract: Endo-1,4-␤-D-glucanases (EGases, EC 3.2.1.4) are enzymes produced in bacteria, fungi, and plants that hydrolyze polysaccharides possessing a 1,4-␤-D-glucan backbone. All previously identified plant EGases are E-type endoglucanases that possess signal sequences for endoplasmic reticulum entry and are secreted to the cell wall. Here we report the characterization of a novel E-type plant EGase (tomato Cel3) with a hydrophobic transmembrane domain and structure typical of type II integral membrane proteins. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 31 publications
(47 reference statements)
3
78
1
1
Order By: Relevance
“…In apparent contrast with the in situ immunolabeling results, immunoblotting revealed KOR1 in fractions enriched for plasma membrane markers obtained by sucrose density gradients (Brummell et al, 1997), free-flow electrophoresis (Nicol et al, 1998), or two-phase partitioning (S. Vernhettes, unpublished data). Because no endosomal markers were used in these experiments, it cannot be excluded that these plasma membraneenriched fractions contained membranes of endosomal origin.…”
Section: Discussion Kor1 Endo-14-b-d-glucanase Cycles Through Subcelcontrasting
confidence: 57%
See 1 more Smart Citation
“…In apparent contrast with the in situ immunolabeling results, immunoblotting revealed KOR1 in fractions enriched for plasma membrane markers obtained by sucrose density gradients (Brummell et al, 1997), free-flow electrophoresis (Nicol et al, 1998), or two-phase partitioning (S. Vernhettes, unpublished data). Because no endosomal markers were used in these experiments, it cannot be excluded that these plasma membraneenriched fractions contained membranes of endosomal origin.…”
Section: Discussion Kor1 Endo-14-b-d-glucanase Cycles Through Subcelcontrasting
confidence: 57%
“…In contrast with other endo-1,4-b-D-glucanases, KOR1 is an integral type II membrane protein. Sucrose density gradients on microsomes from tomato (Lycopersicon esculentum) seedlings and free-flow electrophoresis on membranes from Arabidopsis cell suspension cultures localized KOR1 at least partially to the plasma membrane but also to intracellular fractions (Brummell et al, 1997;Nicol et al, 1998). Zuo et al (2000) expressed a KOR1-green fluorescent protein (GFP) fusion protein in tobacco (Nicotiana tabacum) BY2 cells and observed the accumulation of the fusion protein in the nascent cell plate and in punctate intracellular structures.…”
Section: Introductionmentioning
confidence: 99%
“…The tomato (Solanum lycopersicum) GH9A1 homolog Sl-GH9A1 was localized to both the Golgi and the plasma membrane by Suc gradient fractionation of tomato root microsomal membranes (Brummell et al, 1997). Partially consistent with this observation, AtGH9A1-GFP (for green fluorescent protein) showed a punctate pattern in interphase cells and was observed at the cell plate during cytokinesis of tobacco (Nicotiana tabacum) BY2 cells (Zuo et al, 2000).…”
Section: Introductionsupporting
confidence: 62%
“…The latter class can further be divided into two groups depending on whether or not these proteins contain a cellulose-binding domain (CBD) at the C-terminal. It has been previously reported that transmembrane EGs might be related to the biological synthesis of plant cellulose (Libertini et al 2004;Brummell et al 1997), and secreted…”
Section: Discussionmentioning
confidence: 99%